2012
DOI: 10.1177/1538574412449908
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Embolization of Extensive Left Gastric Artery Collaterals Presenting With Massive Upper Gastrointestinal Bleed

Abstract: We report a case of extensive left gastric artery collaterals that were formed in the region of gastric fundus due to splenic artery occlusion and resulted in massive hematemesis. These collaterals were thought to be portosystemic collaterals related to portal hypertension during upper endoscopy study and single-phase venous computed tomography studies. The collaterals were treated by transcatheter endovascular coil embolization. Our case highlights the importance of recognizing and differentiating left gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…No procedure-related major adverse events were observed[ 23 ]. Few years later, another case successfully managed in a very similar manner was described[ 24 ]. Conversely, Al-Balas et al [ 25 ] recently reported a case of bleeding GSAC initially managed via TEA and subsequently requiring emergency laparotomy with ligation of a bleeding gastric vessel and splenectomy due to severe rebleeding occurrence[ 25 ].…”
Section: Discussionmentioning
confidence: 94%
“…No procedure-related major adverse events were observed[ 23 ]. Few years later, another case successfully managed in a very similar manner was described[ 24 ]. Conversely, Al-Balas et al [ 25 ] recently reported a case of bleeding GSAC initially managed via TEA and subsequently requiring emergency laparotomy with ligation of a bleeding gastric vessel and splenectomy due to severe rebleeding occurrence[ 25 ].…”
Section: Discussionmentioning
confidence: 94%